Real estate marketing plan for pt mahika tirta - Wibowo, Sumintong; Fachira, Ira (The Indonesian Journal of Business Administration, 2016)
Abstract - PT Mahika Tirta as a new comer in developer real estate business wants to take opportunity in backlog of house issue.  At this stage company already have lands and through permit and permission process, the block plan already approved, already get bank support and building process in progress. One problem that appears now is this company not have clear marketing plan yet to success selling all the houses. To create impact full marketing plan the company first need to know is their customer behavior through information what customer consider most and from what communication channel customer get information about houses most. To deal with these issues analyzed both external and internal using PESTEL, Porter Five Forces, Competitor Analysis, Marketing Strategy and 7Ps Marketing Strategy Mix which generate SWOT items. To strengthen the analysis researcher also spread questioners to 200 target customers. The proposed marketing plan for Mahika Tirta has been made based on that analysis result. Marketing plan consist of four aspects which are three aspects (Product, Price and Promotion) describe resume of customer’s most consideration and one aspect which is Place describe communication channel that customer use most.  With all that aspect the researcher expects company can have a guide line to run impact full marketing plan and can deliver it to their target customer through effective and efficient communication channel. The most of all, the researcher also expect this marketing plan also can overcome company’s weakness and threat.  Keywords: Developer real estate, Marketing Plan, SWOT, 7Ps Marketing Strategy Mix